The Effectiveness of Anadara Granosa (blood clam shell) and Meretrix Iyrata (white hard clam shell) as Natural Coagulant for the Removal of Turbidity from Synthetic Wastewater - Donal, Dayang Nur Faiza; Abdul Hamid, Nor Hazren (Progress in Engineering Application and Technology, 2024)
Natural coagulant is one of the alternative methods in minimizing the usage of chemical coagulant in water treatment. The natural coagulant use in this study which will be these two types of clams, which is Anadara Granosa (blood clam shell) and Meretrix Iyrata (white hard clam shell). This natural coagulant that was used in the research study is to lessen environmental pollution and support sustainable development by avoiding or lessen the usage of chemical coagulation such as alum. The water parameters such as coagulant dosage and settling time were manipulated in the conventional Jar test experiment to analyze the efficiency of the Anadara Granosa powder and Meretrix Iyrata powder at the end of the study. Results obtained shows that blood clam shell powder with dose of 5g/L, with settling time 60 minutes in initial turbidity of 200 NTU are the ideal values. Blood clam shell powder produced the highest turbidity removal efficiency of 72.1%, 64.6% and 58.4% in settling time 15, 30 and 60 minutes respectively. These findings indicate that the blood clam shell (Anadara Granosa) powder can be used as natural coagulants to remove the turbidity from synthetic wastewater.